PERAN KOMUNITAS DALAM MENINGKATKAN KINERJA UKM (DITINJAU DARI FAKTOR INTERNAL) - Rahmanto, Basuki Toto; Nurjanah, Siti; Darmo, Ika Suhartanti (Economic Faculty, Attahiriyah Islamic University, 2018)
Small medium enterprises have large contribution on an economy, and it’s very important to develop SME in numbers and quality since SME may provide new income for society, especially in Indonesia which has small proportion of enterpreneurs. Firm performance, has been studied by many researchers and it’s very interesting topics because every organization wants to achieve the best performance. To improve their performance, organization (including SME) need to enhance their knowledge, that they can get by join some enterpreneur community. Tangan Di Atas (TDA) ia one of the largest enterpreneur community in Indonesia which has many activities to develop their members. This study aims to analize the effect of internal factors on SME performance that become TDA member. The result of this study shows that internal factors effects the SME performace. Keywords: Internal Factor, SME’s performance